2021
DOI: 10.1136/bmjopen-2020-046350
|View full text |Cite
|
Sign up to set email alerts
|

Depression and anxiety symptoms to COVID-19 outbreak among the public, medical staff and patients during the initial phase of the pandemic: an online questionnaire survey by a WeChat Mini Program

Abstract: ObjectivesTo survey anxiety and depression symptoms to COVID-19 outbreak in the public, medical staff and patients during the initial phase of the pandemic.DesignCross-sectional online survey administered through WeChat Mini Program using Chinese versions of Zung Self-rating Depression Scale and Zung Self-rating Anxiety Scale.SettingGuangzhou, China.Participants47 378 public, 1512 medical staff and 125 patients with COVID-19.ResultsHigher rates of depression (47.8%) and anxiety symptoms (48.7%) were shown by p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 26 publications
1
13
1
Order By: Relevance
“…Those with increased contact with COVID-19 infected individuals exhibited stronger associations with anxiety [ 45 , 87 , 94 ], especially if the individual was exposed to COVID-19 in a working environment such as healthcare [ 56 , 67 ]. Populations infected with COVID-19 expressed more anxiety than those who were not infected [ 44 , 56 , 61 , 102 ]. Job loss or financial hardship due to COVID-19 was often a predictor or factor for worse anxiety [ 39 , 93 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Those with increased contact with COVID-19 infected individuals exhibited stronger associations with anxiety [ 45 , 87 , 94 ], especially if the individual was exposed to COVID-19 in a working environment such as healthcare [ 56 , 67 ]. Populations infected with COVID-19 expressed more anxiety than those who were not infected [ 44 , 56 , 61 , 102 ]. Job loss or financial hardship due to COVID-19 was often a predictor or factor for worse anxiety [ 39 , 93 ].…”
Section: Resultsmentioning
confidence: 99%
“…Certain demographic groups were identified as having a higher prevalence of anxiety or being more at risk of developing adverse mental health issues. Twenty-two studies found that females consistently had higher levels of anxiety than males [ 11 , 28 , 31 , 32 , 33 , 35 , 39 , 41 , 62 , 63 , 65 , 75 , 79 , 82 , 86 , 88 , 92 , 94 , 96 , 102 , 105 , 110 ]. However, two studies found that males were more anxious when living with dependents under 18 [ 50 , 61 ] and that younger males had higher instances of anxiety [ 56 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the repeated local suppression of the epidemic, coupled with the relaxation of measures and the simultaneous emergence of new mutations of the coronavirus (Torjesen, 2021) which again increase the spread of the virus and lead to the reintroduction of measures creates a state of uncertainty with little possibility of predicting future developments. This multitude of changes, the fear of COVID-19 and the uncertainty about the future course of the pandemic also has a significant negative impact on the mental health of the population, as confirmed by a number of studies (e.g., Lakhan et al, 2020;Novotný et al, 2020;Rossi et al, 2020;Bueno-Notivol et al, 2021;Wang et al, 2021). The impact on mental health is also related to the degree of personal experience of the pandemic and how much change the pandemic and the restrictions have caused in personal life.…”
Section: Introductionmentioning
confidence: 90%
“…Based on previous studies, standardized score between 50-59, between 60-69, and ≥70 represented mild, moderate, and severe anxiety level, respectively ( Zhu et al., 2021 ). The Chinese version of SAS showed good reliability and validity ( Gao et al., 2012 ; Li et al., 2021a ; Wang et al., 2021b ). In this survey, Cronbach's α coefficient of internal consistency of this scale was 0.840.…”
Section: Methodsmentioning
confidence: 99%